Прізвиська жителів Волинського Полісся, ідентичні з варіантами власних особових імен - Нестерчук, Оксана Григорівна; Nesterchuk, Oksana H. (My University, 2014)
У статті проаналізовані неофіційні найменування жителів Волинського Полісся, мотивовані власними іменами їхніх батьків та “дальших” родичів. Виявлено творення прізвиськ за допомогою загальновживаних зменшено-пестливих та збільшено-згрубілих суфіксів. Неофіційні назви найчастіше мають “нейтральний” зміст, хоч зрідка виконують ідентифікувальну функцію стосовно конкретного носія. The article considers the nicknames, identical with variants of names of residents of Volyn Polissya, which are directly linked with the name of father, mother, grandmother, grandfather or someone from the ancestors. Material for the study served as the unofficial names of the parties contained in three-volume «Dictionary of nicknames of northwest Ukraine» served. For comparison with the variants of the names used records of the author from 140 settlements in Volyn Polissya. On frequency of use among the informal names established the largest number education on behalf of the father and the grandfather, using generally accepted suffixes. There was also a nickname granted to holders for their actions, external details, nature, specific pronunciation associated with variants of names, who are residents of Volyn Polissya. Some names homonymic, however have various motivation.
Nicknames Volyn Polissya, identical personal names and versions
Keywords: прізвиська суфіксація; неофіційні найменування; власні особові імена; варіанти імен; суфіксація; nicknames; unofficial names; proper personal name; name option; suffiksation